2004
DOI: 10.1002/app.20794
|View full text |Cite
|
Sign up to set email alerts
|

Filamentous green algae additions to isocyanate based foams

Abstract: ABSTRACT:Filamentous green algae, Cladophora glomerata, obtained from rivers and streams in California was used as a filler in isocyanate-based foams. Up to 40 wt % dried and chopped algal fibers were added to the isocyanate-polyol mix. The algal fibers and foam samples were examined by scanning electron microscopy. The effective hydroxyl number of the algae and the tensile and compressive properties of the composite foam were measured. The results indicate that foams with a uniform cell size were obtained for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…The Young's modulus of various grades of Mater-Bi Ò , poly(e-caprolactone) and polyhydroxybutyrate was improved with the addition of Ulva armoricana particles of 50-100 lm [7] and algae from Sardinia beaches (not specified) [6]. Green algae (Cladophora) fibres, having average length of around 600 lm, have also been successfully used in the preparation of isocyanate based foams [8]. The notion of algae as filler for thermoplastics has been also exhibited through international patents [9,10].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The Young's modulus of various grades of Mater-Bi Ò , poly(e-caprolactone) and polyhydroxybutyrate was improved with the addition of Ulva armoricana particles of 50-100 lm [7] and algae from Sardinia beaches (not specified) [6]. Green algae (Cladophora) fibres, having average length of around 600 lm, have also been successfully used in the preparation of isocyanate based foams [8]. The notion of algae as filler for thermoplastics has been also exhibited through international patents [9,10].…”
Section: Introductionmentioning
confidence: 95%
“…Two main approaches in using algae in composites have been reported: first, as fillers (not treated, only milled and pulverised) with the goal to decrease both the price and carbon footprint of polymer and utilise algae waste [1,[5][6][7][8][9][10] and second, as reinforcing fibres (treated, usually bleached, to keep mainly cellulosic fibres and remove soluble compounds) [11][12][13]. For example, bleached red algae was melt-mixed with poly(lactic) acid (PLA) and polypropylene [11] and poly(butylene succinate) [12] resulting in their improved mechanical properties and the coefficient of thermal expansion.…”
Section: Introductionmentioning
confidence: 99%
“…The natural reason for the presence of highly crystalline cellulose microfibrils in the cell walls of marine green algae featured with exceptionally high density is not clear. It has been suggested that strong microfibrils in Cladophora cell walls are necessary to withstand the drag flow from water 70. Alternatively, strong cellulose microfibrils may be needed to maintain the turgor (i.e., osmotic pressure inside cells) in an environment that features fluctuating salinity 71…”
Section: Mechanical Properties Of Cladophora Algae Cellulosementioning
confidence: 99%
“…Although cellulose nano whiskers were not discussed, it proved that a high aspect ratio, one of the characteristics of whiskers, had a considerable positive effect on the improvement of mechanical properties. Green algae cellulose fibers of 500 to 600 µm in length and 20 to 200 µm in width were used to prepare a PU composite foam by Johnson & Shivkumar (2004). It was reported that the peak mechanical of properties the composite foams were obtained at a dry fiber content of 5-10 wt%, while a maximum of 40 wt% incorporation, based on the total weight of isocyanate and polyol, were investigated.…”
Section: Cellulose Fiber and Microfibril Reinforced Polyurethanementioning
confidence: 99%